Evaluation of the ability of calcite, bentonite and barite to enhance oil dispersion under arctic conditions. (February 2018) - Jézéquel, Ronan; Receveur, Justine; Nedwed, Tim; Le Floch, Stéphane
Abstract: A test program was conducted at laboratory and pilot scale to assess the ability of clays used in drilling mud (calcite, bentonite and barite) to create oil-mineral aggregates and disperse crude oil under arctic conditions. Laboratory tests were performed in order to determine the most efficient conditions (type of clay, MOR (Mineral/Oil Ratio), mixing energy) for OMA (Oil Mineral Aggregate) formation. The dispersion rates of four crude oils were assessed at two salinities. Dispersion was characterized in terms of oil concentration in the water column and median OMA size. Calcite appeared to be the best candidate at a MOR of 2:5. High mixing energy was required to initiate OMA formation and low energy was then necessary to prevent the OMAs from resurfacing. Oil dispersion using Corexit 9500 was compared with oil dispersion using mineral fines. Highlights: The ability of mineral fines to create oil-mineral aggregates was investigated under arctic conditions Four crude oils were tested at laboratory and pilot scale to assess theinfluence of the type of mineral fines, MOR, water salinity on OMA formation Tests at pilot scale indicated that barite was not a good candidate for OMA formation. Best results were obtained with calcite, followed by bentonite while barite produced very limited dispersion. Due to high MOR required to observe oil dispersion, the use of mineralfines could be limited to small spills